Efficacy of boom systems in controlling runoff under center pivots and linear move irrigation systems - Nakawuka, Prossie; Okwany, Romulus O.; Peters, R.T.; Desta, K.; Sadeghi, H. (American Society of Agricultural and Biological Engineers, 2014)
Center pivot and linear move irrigation systems’ design and operation are primarily limited by soil infiltration rates. Surface runoff can be a problem on some soils whose in-take rates are low. Additional design and management factors must be considered to prevent runoff in these systems. Boom systems have been suggested to decrease runoff by reducing the water application rate of center pivots and linear move systems. In this study, runoff from plots irrigated with typical in-line sprinklers was compared to runoff from plots irrigated with off-set boom systems. Both inline sprinkler drops and the boom systems were fitted on the same linear move system. Sprinkler nozzle type and size was the same for both in-line drops and the off-set boom drops. Runoff was measured for five irrigation events applied on bare soil during three weeks in October 2013. Differences in runoff between the drop types were significant for the second, third, fourth, and fifth irrigation events. In-line drops generated between 3% and 24% more runoff than the boom systems during the test period. Runoff as a percentage of irrigation water applied increased with each irrigation event for both drop types. The increase however was higher for the in-line drops than for the boom systems. Increase in runoff with increase in sprinkler irrigation events was mainly attributed to soil surface sealing which resulted from sprinkler drop impact.